A Case-Control Study of 3D vs 2D Weightbearing CT Measurements of the M1-M2 Intermetatarsal Angle in Hallux Valgus. (August 2022) - Day, Jonathan; de Cesar Netto, Cesar; Burssens, Arne; Bernasconi, Alessio; Fernando, Celine; Lintz, François
Background: Weightbearing computed tomography (WBCT) 3-dimensional measurements may be reliable in assessing hallux valgus (HV). The objective of this study was to compare 2D and 3D WBCT measurements of the M1-M2 intermetatarsal angle (IMA) in patients with HV and in healthy controls. We hypothesized that 2D and 3D IMA measurements would correlate and have similar reliability in both HV and controls. Methods: Retrospective multicenter comparative study included WBCT scans from 83 feet (41 HV, 42 controls). IMA was measured on digitally reconstructed radiographs (DRR-IMA). 3D angle (3D-IMA) and its projection on the weightbearing plane (2D-IMA) were calculated from 3D coordinates of the first and second metatarsals. Intraobserver reliability and intermethod correlations were calculated using intraclass correlation coefficients (ICCs). Results: Intraobserver reliability was very strong for DRR-IMA (0.95) and 3D-IMA (0.99). Intermethod correlation between the 3 modalities in HV patients ranged from moderate (DRR vs 2D, 0.48; DRR vs 3D, 0.48) to very strong (2D vs 3D, 0.91). Similarly, intermethod correlation in the control group ranged from moderate (DRR vs 2D, 0.56; DRR vs 3D, 0.60) to very strong (2D vs 3D, 0.92). Conclusion: Measurements for IMA are similar using DRR, 3D and 2D projected angles, with very strong intraobserver reliability and moderate to very strong intermethod correlations. This is the first head-to-head comparison between these measurement modalities in HV. Further investigations are warranted before formulating guidelines for the clinical use of 3D angles. Level of Evidence: Level III, case-control study.